A homogenous or heterogeneous audience? Audio description preferences of persons with congenital blindness, non-congenital blindness and low vision. (4th May 2022) - Chmiel, Agnieszka; Mazur, Iwona
ABSTRACT: Audio description (AD) is a type of translation involving the transfer of images into words, whose primary target audience are persons with sight loss. However, in reality audio description users are a heterogeneous group with various dysfunctions ranging from congenital blindness to low vision. These users might differ in their preferences for audio description. In order to investigate this issue, we designed an AD reception study in which we conducted questionnaire-based in-depth interviews with 50 persons with congenital blindness, non-congenital blindness and low vision. The participants watched audio described film clips and answered questions about their preferences regarding general viewing habits, character naming and objectivity, describing facial expressions and colours, using similes and metaphors, explicitation and intertextual allusions. We predicted that the type of vision dysfunction would modulate those group preferences that may be shaped by the existence or lack of residual vision and visual memory, such as video-AD synchronisation or the use of explicitation and intertextual allusions. Our findings suggest that group differences are not as strong as expected. We conclude that AD should strive for middle-of-the-road solutions, at the same time allowing for alternative versions targeted at specific audiences.